School stories : weaving narrative nets to capture science classrooms. - Geelan, David R. (Curtin University, 1998)
Over the past two decades, constructivism has become an increasingly influential referent for the learning and teaching of science in schools. In the role of teacher-researcher, I conducted an intensive participant observational study in an innovative Australian middle school, where both the initial planning of the school program and the principal's vision for the school took constructivism as a key referent. The research activity involved team teaching for a total of two days per week for one school year (1996) with a group of five teachers who were attempting to implement constructivist-referenced innovations such as portfolio assessment, integrated curriculum and teacher collaborative planning in their teaching practice. I chose a narrative methodology including impressionist tales to both conduct and represent this research into my own and others' teaching practices and values - a 'novel' woven from those narratives forms Section Two of this thesis. In addition, five conjectures for further investigation emerged from the research: (1) one significant constraint to constructivist-referenced innovation is 'conceptual inertia' on the part of teachers, (2) students' epistemologies and expectations must be explicitly addressed where innovation is attempted, (3) the complexity of educational contexts extends beyond the mechanical details of schooling to the webs of expectations stakeholders bring to schools, (4) it is difficult for teachers with limited backgrounds in science to use constructivism as a referent in their science teaching, and (5) the narrative methodology chosen has value in providing a rich, complex account of schools, teachers and curricular innovations.